Technical skills errors in laparoscopic cholecystectomy by expert surgeons. - Sarker, S; Chang, A; Vincent, C; Darzi, A (2005)
BACKGROUND: Performing laparoscopic surgery involves a complex cascade of cognitive skills, which may inherently have a constant technical error rate. We assess generic and specific minor and major error rates in laparoscopic cholecystectomies (LCs) performed by consultant surgeons. METHODS: Checklists of generic (11) and specific technical minor (six) and major events (eight) were devised for LCs. Two experienced surgeons assessed each full-length operation blindly and independently. RESULTS: A total of 37 LCs were performed by eight consultants. There were no major intraoperative or postoperative complications. Mean inter-rater reliability was kappa = 0.91 (range 0.80-0.98) for each of the error categories. Error rates were generic (27/407) 6.6%, minor (59/222) 26.6%, and major (8/296) 2.7%, respectively. There was a significant statistical difference between the minor error group and the other groups, p